Impact of intravenous fluid composition on outcomes in patients with systemic inflammatory response syndrome - Shaw, Andrew D.; Schermer, Carol R.; Lobo, Dileep N.; Munson, Sibyl H.; Khangulov, Victor; Hayashida, David K.; Kellum, John A. (BioMed Central, 2015)
Introduction: Intravenous (IV) fluids may be associated with complications not often attributed to fluid type. Fluids with high chloride concentrations such as 0.9 % saline have been associated with adverse outcomes in surgery and critical care. Understanding the association between fluid type and outcomes in general hospitalized patients may inform selection of fluid type in clinical practice. We sought to determine if the type of IV fluid administered to patients with systemic inflammatory response syndrome (SIRS) is associated with outcome.